Development and Parametric Study of B/BaCrO4/FG Pyrotechnic Delay Composition. Issue 5 (4th May 2018) - Khan, Azizullah; Malik, Abdul Qadeer; Lodhi, Zulfiqar Hameed; Hussain, Syed Ammar
ABSTRACT: Studies were undertaken to develop and experimentally investigate the effect of Boron content, Fish Glue (binder) and ambient temperature on the charge consumption and burning rate of Boron/Barium chromate/Fish Glue (B/BaCrO4 /FG) pyrotechnic delay composition in short delay devices together with measurement of exothermicity of delay composition at different fuel/oxidizer ratios. The Boron content was varied from 5% to 45%, while Fish Glue content varied from 0% to 3.0%. The measured burning rate and charge consumption increased with increasing in Boron content until maximum values of burning rate and charge consumption were recorded at 18% boron. Similarly, both burning rate and charge consumption decreased with an increase in binder content and minimum values of these parameters were recorded at 3.0% Fish Glue. The calorific value of this delay mixture also increased with an increase in Boron content until maximum calorific value recorded at about 15% Boron. The composition failed to ignite by the calorimeter as well as by the igniter at Boron contents above 40%. The delay composition filled in delay tubes was then subjected to functional tests after conditioning at a temperature of +70°C, +21°C, and –40°C. The burning rate decreased with decreasing the ambient temperature.